The Relationship Between Spousal Support and Low Interest in Using IUD Contraceptives Among Couples of Childbearing Age at the IBU Community Health Center - Askia Umar; Anik Purwati (Lembaga Pengembangan Kinerja Dosen, 2026)
Every nation, including Indonesia, has a problem with population growth. A high birth rate is the consequence of an expanding population, which causes childhood malnutrition. Family planning is an attempt to regulate the quantity and spacing of children. The AKDR is the recommended method of contraception. Indonesia's AKDR coverage is still inadequate. Because the husband is the head of the household, his support is crucial since he has the power to decide whether or not to use contraception. At the Ibu Community Health Center, this research aims to explore the connection between husband support and a lack of interest in using IUD contraception among couples of reproductive age. With 25 individuals in the study group, a cross-sectional research design with total sampling methodologies was employed. A survey was used as the research method, and the data was subjected to Chi-Square analysis with SPSS. The chi-square statistical test produced a P-value (asymp. Sig 2-tailed) of 0.000 < 0.05, indicating that there is a correlation between husband support and a low desire among couples of reproductive age to utilize IUD contraception. Consequently, since H0 was disproved and H1 was proven, it can be inferred that there is a link between husband support and couples of childbearing age having a low interest in using IUD contraception.